Upaya Peningkatan Hasil Belajar Siswa Dengan Menggunakan Model Pembelajaran Discovery Learning - SRI RAHAYU; Herawati; Diana Puspasari; Riswan Jaenudin; Siti Fatimah (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2024)
This classroom action research aims to determine and describe the use of Discovery Learning Model in improving Accounting learning outcomes for students of class XII IPS 2 at SMAN 1 Unggulan Muara Enim. The research subjects were 27 students in class XII IPS 2, consisting of 12 male students and 15 female students, odd semester for the 2022 - 2023 academic year. The result of the research shows that the Discovery Learning can improve learning outcomes in Accounting for students. The number of students who experienced completion in learning Accounting in the pre-action condition was only 11 students or 41%, then increased in cycle I to 21 students or 78% and in cycle II it was 26 students or 96%. Teachers in carrying out learning should use learning model that provides learning motivation to students and are able to apply them well in the classroom to create an interactive learning atmosphere, thus having an impact on increasing students learning outcomes.